SUSTAINABLE SOLUTIONS: ADVANCING IN TECH-BASED ESG REPORTING PLATFORMS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
Sustainability reporting plays a crucial role in promoting ethical conduct, managing risks, and enhancing stakeholder engagement for businesses aiming for long-term success. Recent changes in European legislation, particularly the Corporate Sustainability Reporting Directive (CSRD), signal a significant shift towards aligning sustainability reporting with financial reporting to meet Sustainable Development Goals. Concurrently, advancements in Environmental, Social, and Governance (ESG) reporting processes have led to the emergence of tech-based platforms, leveraging artificial intelligence (AI), to streamline data gathering and compliance efforts among EU companies. This paper examines the potential impacts of such platforms, focusing on their role in facilitating ESG information collection for regulatory compliance. Utilizing secondary sources such as European legislative acts and relevant literature, the study also presents a case study of "Ecomate ESG platform" as an illustrative example. In addition to regulatory compliance, these platforms offer benefits such as improved efficiency and enhanced stakeholder engagement. The conclusion draws upon key findings to propose general recommendations for the future development of the ESG sector and the effective utilization of AI within it.;